Experimental structure-borne energy flow contribution analysis for vibro-acoustic source ranking. (15th January 2019) - Acri, A.; Nijman, E.; Conrado, E.; Offner, G.
Highlights: Multi-point and multi-DOF experimental energy flow analysis. NVH assessment and ranking of vibro-acoustic sources done investigating energy quantities. Finite difference methodology definition to estimate excitations and velocities. Case study application on a gearbox-like structure. Abstract: Noise legislations and the increasing customer demands determine the NVH (Noise Vibration and Harshness) development of modern commercial vehicles. In order to meet the stringent legislative requirements for the vehicle noise emission, exact knowledge of all vehicle noise sources and their acoustic behavior is required. The development of new analysis tools to investigate the vibroacoustic behaviour within vehicle development process is of essential importance to achieve better products in combination with time and cost reduction. This paper discusses the application of an experimental multi-point and multi-DOF energy flow analysis (EFA) methodology for the NVH assessment and ranking of vibro-acoustic sources. The methodology consists of two steps in which the system mobility matrix are obtained by direct measurements whereas the dynamic loads under operational conditions are obtained through an inverse procedure. A finite difference technique is used to distinguish between degrees of freedom. A practical example is given for a gearbox, for which the noise paths from the gears through the gear-supporting shafts and bearings into the gearbox housing has been experimentally assessed in terms of energy flows. This paper also discusses the accuracy and limits of the methodology.